2010
DOI: 10.1021/nl100030e
|View full text |Cite
|
Sign up to set email alerts
|

Facts and Artifacts in the Blinking Statistics of Semiconductor Nanocrystals

Abstract: Since its initial discovery just over a decade ago, blinking of semiconductor nanocrystals has typically been described in terms of probability distributions for durations of bright, or "on," states and dark, or "off," states. These distributions are obtained by binning photon counts in order to construct a time series for emission intensity and then applying a threshold to distinguish on states from off states. By examining experimental data from CdSe/ZnS core/shell nanocrystals and by simulating this data ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
182
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(194 citation statements)
references
References 40 publications
12
182
0
Order By: Relevance
“…3a). Although it has been shown that blinking statistics are threshold dependent when the threshold is varied significantly 16,20,24 , our analysis confirms that the trends reported here hold for a wide range of reasonable thresholds (see detailed analysis of on-times for different thresholds in Methods). All results reported in the main paper were determined using a threshold of m dark + 7σ dark (red line in Fig.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…3a). Although it has been shown that blinking statistics are threshold dependent when the threshold is varied significantly 16,20,24 , our analysis confirms that the trends reported here hold for a wide range of reasonable thresholds (see detailed analysis of on-times for different thresholds in Methods). All results reported in the main paper were determined using a threshold of m dark + 7σ dark (red line in Fig.…”
Section: Resultssupporting
confidence: 86%
“…Although it has been shown that blinking statistics are threshold dependent when the threshold is varied significantly 16,20,24 , our analysis confirms that the trends reported here hold over the entire threshold range tested, that is, from m dark + 5σ dark up to m dark + 8σ dark , while the absolute on-and off-time durations in the main paper depend on the exact threshold chosen, with higher thresholds yielding effectively shorter on-times (Fig. 8a).…”
Section: Methodssupporting
confidence: 83%
See 1 more Smart Citation
“…Parameters were not subtracted from an actual fit to the experimental WTDs due to their strong dependence on the choice of threshold. 14,17 The values of the shortest on and off timescales (t b(d) m ) have not been separately determined in experiment, and they were chosen to be identical and in the millisecond range. The possibility of lower t b(d) m cannot be ruled out as there is evidence that intensity fluctuations in CdSe/ZnS QDs may extend to 1/10 of a millisecond.…”
Section: Discussion and Comparison With Experimentsmentioning
confidence: 99%
“…It was shown that both of these statistics can be highly biased by the two artificial quantities introduced during the analysis procedure, the bin time and intensity threshold. 14 While binned photon counting statistics have been calculated for exponential WTDs, 15 other relevant WTDs such as power laws and stretched exponentials have not yet been treated. This problem is tackled here by introducing a special kinetic scheme through which the functional form of the WTDs can be controlled.…”
Section: Introductionmentioning
confidence: 99%